Narrative Structure of Storytelling: Digital Storytelling on Youtube Platform - Ndandara, Alfriani; Ludji, Ifoni (Journal of Language, Education, Literature, and Culture, 2025)
This study analyses the transformation of the traditional three-act narrative structure (introduction–confrontation–resolution) in digital storytelling content on the YouTube platform, focusing on seven stories adapted from classic fairy tales (The Wind and the Sun, The Little Red Hen, The Bird and the Whale, The Three Little Pigs, Beauty and the Beast, The Ugly Duckling, and Jack and the Beanstalk). The research uncovered three main findings through a descriptive qualitative approach and narrative analysis. First, the three-act structure remains the dominant framework, but undergoes creative adaptations such as duration compaction (3-10 minutes), the use of instant hooks, and multimedia integration (animation, sound effects) to suit the needs of digital platforms. Second, the variation in conflict in the confrontation round is divided into physical (44%), emotional (29%), and moral (27%) conflicts, which encourage character transformation through physical (100%), moral (83%), and social (71%) dimensions. Third, digital innovations such as narrative visuals (72%), interactivity (38%), musicalization (65%), and non-linearity of plot (27%) revolutionize storytelling without abandoning the essence of traditional narratives. The theoretical implications of the research include the need for a hybrid analytical framework that combines classical narratives with the characteristics of digital media, while the practical implications confirm the effectiveness of YouTube content for language learning (78% higher than conventional texts) and guidance for creators in designing adaptive storytelling strategies. In conclusion, traditional structures are irreplaceable, but are evolving through flexibility and technical innovation, proving their resilience in a dynamic digital media ecosystem.